The Meaning of Capital in the Perspective of Cultural Norms for Fish Cracker Entrepreneurs in Srowo Village Gresik Regency - Ayu Sari Maulidyah; Rahmat Agus Santoso; Maulidyah Amalina Rizqi (Universitas Muhammadiyah Gresik, 2022)
The background in this research is the idea of ​​being able to return business capital from existing capital in Srowo Village. This study aims to examine the meaning of capital in the perspective of customs and the meaning of capital in the perspective of folkways or habits of cracker entrepreneurs in Srowo Village, Gresik Regency. This study uses a qualitative method. The subjects in this study were Fish Cracker Businesses in Srowo Village, Gresik Regency, while the sampling used the Non Probability Sampling technique using Purposive Sampling. The reason is because sampling has more characteristics or generalizations. The sample studied by the researcher was Mr. Kinun as the village apparatus in Srowo Village and also one of the cracker entrepreneurs who the researchers used as the gatekeeper, the first person as the researcher's data source who understands and has experience. The analysis technique uses data collection methods through interviews, data reduction, data presentation, and verification. The results of this study indicate that obedience is caused by devotion to ancestors by preserving inheritance which can be used as a business opportunity in carrying out obligations to earn a living. Innovation profit due to business success from investment and achievement in their business continuity.